P-386 Serum P levels measured on the day of embryo transfer in FET modified natural cycles are not related to pregnancy outcome. (30th June 2022) - Labarta, E; Rodriguez-Varela, C; Vidal, C; Doblinger, J; Alamá, P; Marzal, A; Cruz, F; Giles, J; Bellver, J; Romero, J.L; Olmo, I; Gómez, V.H; et al.
Abstract: Study question: Is there an optimal serum progesterone (P) threshold in frozen embryo transfer (FET) modified natural cycles when luteal phase support (LPS) is given? Summary answer: Serum P measured on the day of ET is not related with ongoing pregnancy outcome when doing a modified natural cycle with LPS. What is known already: Recent publications showed that there is a minimum threshold of serum P that needs to be reached in artificial cycles to optimize pregnancy rates. When using micronized vaginal P (MVP), about 30% of patients show low levels of serum P (<9 ng/mL) leading to a significant decrease in ongoing pregnancy; although this situation can be reverted by increasing and modifying the route of exogenous P. In pure natural cycles without LPS, serum P below 10 ng/mL impairs pregnancy outcome. Nevertheless, there is no data about the impact of serum P levels in modified natural cycles in which LPS is given. Study design, size, duration: Prospective cohort unicentric study performed in IVI RMA Valencia (Spain), including 244 cycles from February 2020 to January 2021. Participants/materials, setting, methods: Infertile patients <50 y.o. and BMI<40Kg/m 2 undergoing a FET of a maximum of 2 blastocysts, from own or donated oocytes. FET were performed in the context of a modified natural cycle (single injection of rec-hCG when dominant follicle reached 17mm and endometrial thickness >6.5mm). MVP was used for LPS (200mg/12h). Ongoing pregnancy rate (OPR) was correlated with serum P levels on the FET day, measured within two hours before transfer. Main results and the role of chance: A total of 241 patients were analyzed. Mean age was 38.1 + 3.8 years, with a mean BMI of 23.3 + 3.9. On the rec-hCG day the mean leading follicle size was 17.7±0.1 mm. The endometrium displayed a trilaminar pattern, with a mean thickness of 7.8±3.3 mm, and mean P and estradiol (E2) levels were 0.30±0.03 ng/ml and 249.39±11.03  pg/ml, respectively. A mean of 1.1 blastocysts were transferred (90.9% were single embryo transfers), 27.4% (66) from donated and 72.6 % (175) from own oocytes. On the day of FET, the mean serum P and E2 levels were 26.19 + 8.97ng/mL and 154.12 + 96.08pg/mL, respectively. The overall OPR was 51.5% (124). OPR according to quartiles of serum P (ng/mL) was 56.7% (Q1, P < 20.2), 47.5% (Q2, P > 20.2-24.8), 51.7% (Q3, P > 24.8-31.1), 50.0% (Q4, P > 31.1), p = 0.78). Multivariate logistic regression showed that serum P was not related with OPR after adjusting for age, BMI, E2 and origin of oocytes (aOR:0.98, 95% CI:0.93-1.04, p = 0.47). Only 2 patients had serum P levels below 10 ng/mL, with values of 8.6 and 8.8 ng/mL on the ET day and had a negative pregnancy test. Limitations, reasons for caution: As part of our routine clinical practice, MVP (200mg/12h) is given for LPS in patients undergoing a FET in the context of a modified natural cycle. Thus, these results cannot be extrapolated to LPS-free or any other LPS protocol in FET modified natural cycles. Wider implications of the findings: The majority of patients undergoing FET in modified natural cycles when using LPS have adequate levels of serum P and thus, do not have an impact on pregnancy outcome. According to our data, there is no need to measure serum P levels on the luteal phase of modified natural cycles. Trial registration number: NCT04259996